The abscopal effect: mechanism of occurrence and prospects of using it in therapy of metastatic cancer - A. V. Khachaturyan; P. V. Bulychkin (Сибирский онкологический журнал)
The abscopal effect in oncology has been known for 70 years, but until recently its clinical significance was rather low. The development of immune response checkpoint inhibitors has led to an active study of this phenomenon. There is now evidence of improved survival among patients, in whom the abscopal effect has been documented, opening new perspectives for the treatment of cancers at different stages. This review presents data on the mechanisms of the abscopal effect, experimental and clinical data, current limitations and possible perspectives. The aim of the study was to investigate the current concept of the abscopal effect occurrence and to evaluate the prospects of using the abscopal effect in therapy of metastatic cancer. Material and Methods. We searched publications in Pubmed system from 2010 to 2023. Of 286 publications, 72 were used for writing the review. Results. In the era of widespread use of immune checkpoint inhibitors (ICIs) for cancer therapy, the abscopal effect appears to be an effective therapeutic approach with broad prospects of application in the treatment of patients with metastatic cancer. Conclusion. The incidence of the abscopal effect has increased with the advent of immune therapy, and the use of ICIs with radiation therapy (RT) has shown improved survival even in patients with advanced disease. More research is needed to establish standardized treatment protocols, including the optimal dose and timing of RT, as well as the efficacy and safety of combination therapy with different classes of ICIs. Further search for clinical and laboratory abscopal effect predictors, which could allow personalized treatment approaches, is required.